Daily variations of the antioxidant defense system of the lithodid crab Lithodes santolla - Schvezov, Natasha; Lovrich, Gustavo Alejandro; Tapella, Federico; Romero, Maria Carolina (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology)
Several physiological processes can induce daily variations in aerobic metabolism. Lithodes santolla is a decapod crustacean of special concern since it is a sub-Antarctic species of commercial interest. The aim of this work was to study in L. santolla the daily variations in levels of enzymatic and non-enzymatic antioxidants, lipid peroxidation and protein oxidation, and haemolymphatic pH. Males of L. santolla of commercial size were randomly dissected every 4 h during a period of 24 h. Enzymatic activities of superoxide dismutase (SOD), catalase (CAT), glutathione-S-transferase and glutathione peroxidase were determined in samples of gills, muscle, hepatopancreas and haemolymph. Ascorbic acid, total glutathione, lipid peroxidation and protein oxidation were also determined in all tissues. Gills showed the highest enzymatic activity and hepatopancreas the highest concentration of non-enzymatic antioxidants. Maximum antioxidant activity was during the dark phase in gills and during the photophase in the haemolymph. Muscle showed significant daily variations, with peaks during the photophase and scotophase. Overall, an antioxidant protective mechanism is present in all tissues, where SOD and CAT represent the first line of defense. The defense mechanism in L. santolla seems to be more active during the dark phase, with slight differences among the analyzed tissues, indicating a higher metabolic rate. Fil: Schvezov, Natasha. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Lovrich, Gustavo Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Tapella, Federico. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Romero, Maria Carolina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina